Application and development of optical fibre sensing system using light spectra analysing technique for agro-technology industry - Chen, Jun Wei. (2008)
The development in the field of agrotechnology in Singapore, together with its high labor cost and limited land area has led to the need of intensive agriculture. High yield within a limited land area and shortest possible time span yet utilizing minimum resource is required. Intensive agriculture is the production of farm-stocks within a controlled environment, whether it be poultry or vegetable crops. One of the major difficulties lies in simulating the habitat parameters. As such, there is a necessity for close monitoring of essential, identified parameters and to control them within permissible limits. This has resulted in a new field of technology known as precision agriculture. This thesis presents the application of optical fiber sensors in precision agriculture involving two areas: hydroponics environment and aquaculture.